Artificial high‐density lipoprotein‐mimicking nanotherapeutics for the treatment of cardiovascular diseases. (14th July 2021) - He, Hongliang; Hong, Kristen; Liu, Lisha; Schwendeman, Anna
Abstract: Despite the ability of current efficacious low‐density lipoprotein‐cholesterol–lowering therapies to reduce total cardiovascular disease (CVD) risks, CVD still poses major risks for morbidity and mortality to the general population. Because of the pleiotropic endothelial protective effects of high‐density lipoproteins (HDL), the direct infusion of reconstituted HDL (rHDL) products, including MDCO‐216, CER001, and CSL112, have been tested in clinical trials to determine whether direct infusion of rHDL can reduce coronary events in CVD patients. In addition to these rHDL products, in the past two decades, there has been an increased focused on designing artificial HDL‐mimicking nanotherapeutics to produce complementary therapeutic strategies for CVD patients beyond lowering of atherogenic lipoproteins. Although recent reviews have comprehensively discussed the developments of artificial HDL‐mimicking nanoparticles as therapeutics for CVD, there has been little assessment of "plain" or "drug‐free" HDL‐mimicking nanoparticles as therapeutics alone. In this review, we will summarize the clinical outcomes of rHDL products, examine recent advances in other types of artificial HDL‐mimicking nanotherapeutics, including polymeric nanoparticles, cyclodextrins, micelles, metal nanoparticles, and so on; and potential new approaches for future CVD interventions. Moreover, success stories, lessons, and interpretations of the utility and functionality of these HDL‐mimicking nanotherapeutics will be an integral part of this article. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Cardiovascular Disease Abstract : The types of HDL mimics and HDL‐mimicking nanoparticles.